Penanaman Nilai-Nilai Melalui Konseling Anak Usia Dini - Efrida Mandasari Dalimunthe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Counseling is a process in helping students to develop optimally, including personal, social, academic and career development. In Indonesia, the implementation of counseling is carried out by early childhood education teachers, so teachers should deepen the understanding of early childhood counseling. Implementation of counseling guidance in early childhood using media / activities according to the type and development, and according to the age of the students.